Fiber‐optic whispering‐gallery‐mode magnetic field sensor based on magnetic fluid infiltrated hollow core fiber. Issue 9 (9th June 2021) - Zhang, Junying; Tian, Chen; Wang, Ruohui; Chen, Haibin; Zhang, Xiongxing; Guo, Zilong; Wang, Wei
Abstract: A fiber‐optic magnetic field sensor based on magnetic fluid (MF) infiltrated hollow core fiber (HCF) was proposed. The MF infiltrated HCF was used as a micro‐capillary ring resonator, in which, whispering‐gallery modes (WGMs) were exited through a closely placed tapered fiber. Through the intensity modulation introduced by external magnetic field on the resonance dip of the WGM excited in the MF infiltrated HCF, magnetic field measurement can be realized through a cost‐effective way. Experimental results demonstrated a magnetic field linear measurement range of 40–140 Oe, and a sensitivity of 0.04 dB/Oe.